Day 2 Wed, June 08, 2016 2016
DOI: 10.2118/180736-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Multiphase Behavior for n-Butane/Bitumen/Water Mixtures

Abstract: Steam-solvent coinjection has been studied and pilot-tested as a potential method to improve steam-assisted gravity drainage (SAGD) for bitumen recovery. Reliable design of coinjection requires reliable PVT data for bitumen/solvent/water mixtures, which are scarce and fragmentary in the literature. The main objective of this research was to present a new set of PVT and multiphase data for n-butane/Athabasca-bitumen/water mixtures at pressures up to 10 MPa and temperatures up to 160°C. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Gao et al measured multiphase behavior of n ‐butane/bitumen/water mixtures, and observed the complex phase transitions from WL 2 to WL 1 L 2 to WL 1 L 2 V with decreasing pressure at temperatures 353–433 K. They showed that the PR EOS was not able to accurately represent the WL 2 /WL 1 L 2 boundary for 37.02 mol % n ‐butane + 0.96 mol % bitumen + 62.02 mol % water (“Mixture C” in Gao et al) below 393 K. They observed emulsion for this mixture. In this subsection, the CPA EOS is applied to match the experimental phase boundaries.…”
Section: Case Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Gao et al measured multiphase behavior of n ‐butane/bitumen/water mixtures, and observed the complex phase transitions from WL 2 to WL 1 L 2 to WL 1 L 2 V with decreasing pressure at temperatures 353–433 K. They showed that the PR EOS was not able to accurately represent the WL 2 /WL 1 L 2 boundary for 37.02 mol % n ‐butane + 0.96 mol % bitumen + 62.02 mol % water (“Mixture C” in Gao et al) below 393 K. They observed emulsion for this mixture. In this subsection, the CPA EOS is applied to match the experimental phase boundaries.…”
Section: Case Studiesmentioning
confidence: 99%
“…The bitumen density and vapor pressure data given in Gao et al are used to characterize four pseudo components PC1, PC2, PC3, and asphaltene. Table summarizes the parameters for the CPA EOS model.…”
Section: Case Studiesmentioning
confidence: 99%
See 3 more Smart Citations